Application of a novel 2D cadmium(ii)-MOF in the formation of a photo-switch with a substantial on–off ratio1. Issue 65 (21st August 2015) - Roy, Sumit; Dey, Arka; Ray, Partha Pratim; Ortega-Castro, Joaquín; Frontera, Antonio; Chattopadhyay, Shouvik
<x xml:space="preserve">Abstract</x> Single crystal X-ray crystallography of a novel thiocyanate bridged 2D MOF has been reported along with its applicability in photosensitive devices. The band gap in the solid state has been determined and compared with the theoretical value.